Elimination of the data-dependent defects by doubling the frequency of driving signals for cholesteric LCDs - Rybalochka, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Using the standard waveform composition method for 2+2 dynamic drive schemes results in the dependence of image contrast on image data-content. In this paper, an implementation of this standard method with doubling the frequency of driving signals is proposed. It allows to equalize the effective selection time for all display’s pixels independently of preceding and following non-selected pixel voltage waveforms. Thus, data-pattern-dependent defects at the passive-matrix addressing of cholesteric liquid crystal displays are fully eliminated.